Flow duration curves and sediment yield estimation for urbanizing watersheds - Rosburg, Tyler Thomas, author; Nelson, Peter A., advisor; Bledsoe, Brian P., advisor; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2015)
Land use change associated with urbanization can alter natural flow regimes, typically resulting in larger peak flows for a given precipitation event than in a pre-urbanized watershed condition. The overall influence of urbanization on how flows of different frequencies might change over time, while important in hydrologic design, remains poorly understood. In this study, we first investigate the effects of urbanization on flow duration curves (FDCs) and flow variability through a case study of several watersheds in the Puget Sound Region of Washington State. A FDC is a graphical representation of the frequency, or fraction of time, that a discharge magnitude is equaled or exceeded. Using different time windows of the flow record, we analyzed stream discharge, precipitation, and watershed urbanization for a minimum of 25 years between 1960 and 2010 to quantify how key FDC percentiles changed with time in response to urbanization in small watersheds (less than 200 km²) with land uses ranging from highly urban to primarily rural. In the urban watersheds, the 95th-99th percentile of the daily-mean flow series increased by 0-94% with an average increase of 35%. The magnitude of small discharges (10th percentile) in the urban watersheds also increased by up to 34% with an average increase of 15%. The rapidity and magnitude of changes in streamflow, commonly known as “flashiness,” was also observed to increase over the period analyzed for both urban and rural watersheds. Flashiness increased by 46% on average in urban watersheds, a result likely caused by increases in population density and impervious surfaces. Rural watersheds were found to have lesser increases in flashiness, 14% on average, attributed to baseflow reductions and increasing precipitation intensity and variability. As watersheds become flashier, the decision to use either daily-averaged or sub-daily streamflow records has the potential to impact the calculation of sediment transport metrics. To investigate, we calculated the effective discharge, sediment yield, and half-load discharge using sediment rating curves over long time periods with both daily-averaged and sub-daily streamflow records, in the second part of this study. The pool of sites in the analysis included 39 sites with bedload measurements and 99 sites with suspended load measurements from several regions of the United States. Results of this analysis were compared to site-specific metrics such as stream flashiness and bed sediment size. A comparison of sediment transport metrics calculated with both daily-average and sub-daily stream flow data at each site showed that daily-averaged flow data were unable to adequately represent the magnitude of high streamflows at flashy sites. This caused an underestimation of sediment transport and sediment yield at flashy sites, the degree of which was controlled by the magnitude of the best-fit exponent of the sediment rating curve. Regression equations are provided for estimating this bias as a function of stream flashiness and sediment rating curve parameters. No relationship between flow data resolution and effective discharge was found. The results of this analysis help inform the use of FDCs and sediment yield estimation in urbanizing watersheds. This analysis demonstrates the magnitude of change that urbanization may cause in a FDC. Additionally, this analysis illustrates the importance of using sub-daily flow data in the calculation of sediment yield in urbanizing or otherwise flashy watersheds.
Keywords: flow; sediment; yield; hydrology; duration; urbanization